2015
DOI: 10.1088/0953-4075/48/6/065002
|View full text |Cite
|
Sign up to set email alerts
|

Feshbach molecule formation through an oscillating magnetic field: subharmonic resonances

Abstract: The conversion of ultracold atoms to molecules via a magnetic Feshbach resonance with a sinusoidal modulation of the field is studied. Different practical realizations of this method in Bose atomic gases are analyzed. Our model incorporates many-body effects through an effective reduction of the complete microscopic dynamics. Moreover, we simulate the experimental conditions corresponding to the preparation of the system as a thermal gas and as a condensate. Some of the experimental findings are clarified. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Brouard and Plata have recently presented a different theoretical treatment of the association of atoms into dimers using an oscillating magnetic field [11]. They also used a two-channel model for the two-atom system, with one channel consisting of a continuum of positive-energy atom pair states and the second channel consisting of a single discrete molecular state.…”
Section: Comparisons and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…Brouard and Plata have recently presented a different theoretical treatment of the association of atoms into dimers using an oscillating magnetic field [11]. They also used a two-channel model for the two-atom system, with one channel consisting of a continuum of positive-energy atom pair states and the second channel consisting of a single discrete molecular state.…”
Section: Comparisons and Summarymentioning
confidence: 99%
“…However in Ref. [11], a time-dependent unitary transformation was used to move the time-dependence into off-diagonal terms between the dimer state and the atom-pair states. They showed that for frequencies near the harmonic resonance, the dynamics in the transformed frame can be approximated by a time-independent Hamiltonian whose entries are given analytically as functions of the oscillation parameters and the Feshbach resonance parameters.…”
Section: Comparisons and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Namely, we concentrate on the variation of the effective coupling constant that can be achieved with the proposed arrangements of magnetic fields. Additional aspects of the dynamics, which can limit the conversion efficiency, were analyzed for the case of single-frequency field in [22].…”
Section: A General Approachmentioning
confidence: 99%